(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Incidence of craniocerebral injury cases are on the rise year on year in urban as well as in rural population. This study involved all medicolegal autopsies referred from Pravara Rural Hospital or brought dead directly to department of forensic medicine, Rural Medical College, Loni, during the year July 1997 to June 2000. The observations made are represented in this paper.